Nestin-GFP transgene labels immunoprivileged bone marrow mesenchymal stem cells in the model of ectopic foci formation - Karpenko, Dmitriy; Kapranov, Nikolay; Bigildeev, Aleksei (Frontiers in Cell and Developmental Biology, 2022)
Immune privileges are demonstrated for different types of quiescent stem cells of adult mammalian organisms. Mesenchymal stem cells (MSCs) are believed to have immune privileges; however, an accurate experimental confirmation hasn’t been presented. Here, we provide direct experimental evidence that MSCs of C57Black/6J murine bone marrow (BM) are immune privileged in vivo and retain their functionality after prolonged exposure to the uncompromised immune system. The BM of Nes-Gfp transgenic mice was implanted as a tissue fragment under the kidney capsule in isogenic C57Black/6J immunocompetent recipients. Nestin-Gfp strain provides a fluorescent immunogenic marker for a small fraction of BM cells, including GFP+CD45– MSCs. Despite the exposure of xenogenically marked MSCs to the fully-functional immune system, primary ectopic foci of hematopoiesis formed. Six weeks after implantation, multicolor fluorescence cytometry revealed both GFP+CD45– and Nes-GFP+CD45+ cells within the foci. GFP+CD45– cells proportion was 2.0 × 10-5 ×÷9 and it didn’t differ significantly from syngeneic Nes-GFP transplantation control. According to current knowledge, the immune system of the recipients should eliminate GFP+ cells, including GFP+ MSCs. These results show that MSCs evade immunity. Primary foci were retransplanted into secondary Nes-GFP recipients. The secondary foci formed, in which CD45–GFP+ cells proportion was 6.7 × 10-5 ×÷2.2, and it didn’t differ from intact Nes-GFP BM. The results demonstrate that MSCs preserve self-renewal and retain their functionality after prolonged immune exposure. The success of this study relied on the implantation of BM fragments without prior dissociation of cells and the fact that the vast majority of implanted cells were immunologically equivalent to the recipients.